2019
DOI: 10.5194/acp-2019-709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methane Emissions from the Munich Oktoberfest

Abstract: <p><strong>Abstract.</strong> This study presents the first investigation of the methane (CH<sub>4</sub>) emissions of a big festival. In 2018 we measured the CH<sub>4</sub> emissions of Munich Oktoberfest, the world's largest folk festival, using in-situ measurements combined with a Gaussian plume dispersion model. Oktoberfest is a potential source for CH<sub>4</sub> as a high amount o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…As well as cars, bicycles, and child buggies are useful for carrying instruments and batteries, as are backpacks. In a detailed study of emissions around the Munich Oktoberfest in Germany (a major beer festival), Chen et al () made in situ measurements by walking and biking around the perimeter of the Oktoberfest. They then applied a Gaussian plume dispersion model to assess emissions.…”
Section: Quantification Of Emissionsmentioning
confidence: 99%
“…As well as cars, bicycles, and child buggies are useful for carrying instruments and batteries, as are backpacks. In a detailed study of emissions around the Munich Oktoberfest in Germany (a major beer festival), Chen et al () made in situ measurements by walking and biking around the perimeter of the Oktoberfest. They then applied a Gaussian plume dispersion model to assess emissions.…”
Section: Quantification Of Emissionsmentioning
confidence: 99%
“…Several studies have revealed its previously unprecedented high level of performance and stability (Frey et al, 2015(Frey et al, , 2019Sha et al, 2020). In addition, the portability of the EM27/SUN spectrometer favours campaign use, and a series of such campaigns have already successfully been conducted by various investigators (Hase et al, 2015;Hedelius et al, 2016;Butz et al, 2017;Viatte et al, 2017;Chen et al, 2016Chen et al, , 2020Kille et al, 2019;Vogel et al, 2019;Luther et al, 2019;Makarova et al, 2021;Jones et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Conducting mobile sensing requires specialised equipment. There are a few basic requirements of the mobile sensing method; the first is a vehicle, although bicycles can be used (Chen et al, 2020). Electric cars would be ideal, however, due to the current lack of range, petrol cars are often used.…”
Section: Mobile Sensing Methodsmentioning
confidence: 99%
“…Because of this, the parts of an urban area that are surveyed must be carefully selected. There are two main approaches to this problem; the first is to methodically map all parts of the urban area (Maazallahi et al, 2020;von Fischer et al, 2017), or to target known or assumed emission sources multiple times (Albertson et al, 2016;Chen et al, 2020) to get a better quantification of emission sources. Both approaches have their benefits, the targeted approach can better quantify emissions by measuring emissions multiple times at different times of days, and on different days (Chen et al, 2020).…”
Section: Mobile Sensing Methodsmentioning
confidence: 99%
See 1 more Smart Citation